Numerical analysis on heat transfer in parallel-flow rectangular recuperators with internal recycle. - Yeh, Ho-Ming (Journal of Applied Science and Engineering)
Heat transfer in parallel-flow rectangular recuperators with internal recycle has been investigated. In contrast to a single-pass device of same size without recycle, considerable improvement in performance is achievable if one of the flow channels, either heated-fluid phase or cooled-fluid phase, is divided into two subchannels of same width with one performed as the cocurrent flow operating subchannel and the other as the countercurrent-flow reflux subchannel which provides the increase of fluid velocity, resulting in reduction of heat-transfer resistance. The improvement in performance by recycling operation increases as flow rate and reflux ratio increase with negligible amount of hydraulic-dissipated energy.